ADENOMATOID TUMORS OF TESTIS AND EPIDIDYMIS CASE REPORT AND LITERATURE REVIEW (Vietnam Journal of Community Medicine, 2022)
Adenomatoid tumors of testis and epididymis is a benign tumor that is not uncommon. Manycases having orchiectomy were reported because there was no rapid histopathological test.Providing data on diagnosis, treatment, and treatment of the disease, we report a case of a32-year-old man who diagnosed with Adenomatoid tummors of testis and epididymis at theCenter for males and Sexual Medicine-Viet Nam-Germany University Hospital.
Keywords: Adenomatoid tumors of testis and epididymis.